Collaborative Research and Rate of Interests. (December 2015) - Chatterjee, Rittwik; Chattopadhyay, Srobonti
Abstract: This article has made an attempt to link collaborative research in industry with government initiative and market rate of interests. Two firms involved in Cournot competition in the market decide whether to conduct research to devise a technique for cost reduction. The amount of cost reduction after the research and the initial amount of capital possessed by each firm are private information to each of the firms. In particular, both of them have capacity constraint. The objective of this article has been to figure out the impacts of the lending and borrowing rates of interest on collaborative research. In the process, we have studied the effectiveness of different policies to encourage collaborative research and development (R&D).